Loss of Expression of AZGP1 Is Associated With Worse Clinical Outcomes in a Multi‐Institutional Radical Prostatectomy Cohort. Issue 15 (21st June 2016) - Brooks, James D.; Wei, Wei; Pollack, Jonathan R.; West, Robert B.; Shin, Jun Ho; Sunwoo, John B.; Hawley, Sarah J.; Auman, Heidi; Newcomb, Lisa F.; Simko, Jeff; Hurtado‐Coll, Antonio; Troyer, Dean A.; et al.
Abstract : BACKGROUND: Given the uncertainties inherent in clinical measures of prostate cancer aggressiveness, clinically validated tissue biomarkers are needed. We tested whether Alpha‐2‐Glycoprotein 1, Zinc‐Binding (AZGP1) protein levels, measured by immunohistochemistry, and RNA expression, by RNA in situ hybridization (RISH), predict recurrence after radical prostatectomy independent of clinical and pathological parameters. METHODS: AZGP1 IHC and RISH were performed on a large multi‐institutional tissue microarray resource including 1, 275 men with 5 year median follow‐up. The relationship between IHC and RISH expression levels was assessed using the Kappa analysis. Associations with clinical and pathological parameters were tested by the Chi‐square test and the Wilcoxon rank sum test. Relationships with outcome were assessed with univariable and multivariable Cox proportional hazards models and the Log‐rank test. RESULTS: Absent or weak expression of AZGP1 protein was associated with worse recurrence free survival (RFS), disease specific survival, and overall survival after radical prostatectomy in univariable analysis. AZGP1 protein expression, along with pre‐operative serum PSA levels, surgical margin status, seminal vesicle invasion, extracapsular extension, and Gleason score predicted RFS on multivariable analysis. Similarly, absent or low AZGP1 RNA expression by RISH predicted worse RFS after prostatectomy in univariable and multivariable analysis. CONCLUSIONS: In our large, rigorously designed validation cohort, loss of AZGP1 expression predicts RFS after radical prostatectomy independent of clinical and pathological variables. Prostate 76:1409–1419, 2016 . © 2016 Wiley Periodicals, Inc.